Comparative Study between Variable Computer Printed Documents to Identify the Type of the Producing Output Devices - Abeer Sayed Abdo Borae; Yasser Fouad Abd El-Monem Al-Akid; Khaled Abd El-Azeem Mahmoud Tamim; NesrineAbd El-Rahman Mahmoud (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Within the last years, forgery has markedly increased and expanded to encompasscomputers and printers’ usage, their wide evolution facilitated the production of fraudulent printeddocuments by even non-experts. The printers and photocopiers leave their imprints on the produceddocuments. Examination of printed output of a questioned document is essential as it providesinformation about the producing device.This study aims to compare the characteristics of different computer printed documents to identify thetype of the producing output devices (photocopier, inkjet, and laser printers).Methods: 132 documents were typed and printed using different models of inkjet, laser printersand photocopiers. The produced documents were examined with direct light digital microscope andultraviolet light and the printed markings were compared.Conclusion: Our results revealed that each class of the studied printing devices induced specific criteriaon the examined printed documents. These criteria are class characteristics but differ from one type ofdevice to another.